Chandipura virus changes cellular miRNome in human microglial cells. Issue 2 (7th May 2019) - Agrawal, Meghna; Rastogi, Meghana; Dogra, Smriti; Pandey, Neha; Basu, Anirban; Singh, Sunit K.
Abstract: Chandipura virus (CHPV) is a neurotropic virus, known to cause encephalitis in humans. The microRNAs (miRNA/miR) play an important role in the pathogenesis of viral infection. The present study is focused on the role of miRNAs during CHPV (strain 1653514) infection in human microglial cells. The deep sequencing of CHPV‐infected human microglial cells identified a total of 12 differentially expressed miRNA (DEMs). To elucidate the role of DEMs, the target gene prediction, Gene Ontology term (GO Term), pathway enrichment analysis, and miRNA‐messenger RNA (mRNA) interaction network analysis was performed. The GO terms and pathway enrichment analysis provided 146 enriched genes; which were involved in interferon response, cytokine and chemokine signaling. Further, the WGCNA (weighted gene coexpression network analysis) of the enriched genes were discretely categorized into three modules (blue, brown, and turquoise). The hub genes in the blue module may correlate to CHPV induced neuroinflammation. Altogether, the miRNA‐mRNA interaction network and WGCNA study revealed the following pairs, hsa‐miR‐542‐3p and FAF1, hsa‐miR‐92a‐1‐5p and MYD88, and hsa‐miR‐3187‐3p and TNFRSF21, which may contribute to neuroinflammation during CHPV infection in human microglial cells. Highlight: Chandipura virus infects Central Nervous System. Chandipura Virus modulates the microRNA expression pattern in human microglial cells. Chandipura virus affects the cellular gene expression via changes in expression patterns of microRNAs. Chandipura virus infects microglial cells and contributes to the neuroinflammatory events.